High resolution parameter estimation for ultra-wideband MIMO radar - Salmi, J; Sangodoyin, S; Molisch, A F (2010 Conference Record of the Forty Fourth Asilomar Conference on Signals, Systems and Computers, 2010)
In this paper, remote vital sign detection using UWB MIMO radar is investigated. The UWB MIMO channel, which includes the test subject as well as other objects, is modeled as a superposition of propagation paths. Estimation of the path parameters, such as delays and directions, allows to identify and track the breathing pattern, and enable the localization of the target. Modification of the high-resolution RIMAX algorithm (iterative maximum-likelihood estimation scheme) together with a path detection scheme, enables estimation of delay variations of the diaphragm-reflected paths, that are much smaller than the Fourier resolution limits. Furthermore, it is illustrated that with a wideband array model, the requirements for antenna spacing are not as limited as for conventional narrowband array processing. The concept is demonstrated through a controlled experiment using an artificial "breathing" object in an anechoic chamber.